Routledge handbook of drugs and sport - Møller, Verner; Waddington, Ivan; Hoberman, John M. (Routledge international handbooks, 2015)
pt. 1. The construction of the doping problem -- part 2. Drug use in various sports -- part 3. Key cases -- part 4. Anti-doping policy and politics -- part 5. Key themes -- part 6. Approaches to understanding doping in elite sport -- part 7. Drug use outside elite sport.